Characteristics of Dried Yoghurt and Market Test on Adolescent Consumers, Adults and Employees in Bogor City - Monasdir, Monasdir; Irma Isnafia Arief; Zakiah wulandari; Lucia Cyrilla Eko Nugrohowati (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
This study aimed to analyze the characteristics of dried yogurt, market potential, consumer perception, consumer purchasing behavior, and attributes that affect the purchase of dried yogurt made by teenagers, adults and employees in Bogor City. The results showed that based on testing the characteristics of dried yogurt with parameters of water content, pH, Aw, Viscosity, TAT and total lactic acid bacteria dried yogurt is safe for consumption. Based on the results of the conjoint analysis, it shows that to market dried yoghurt, producers must design dried yoghurt with probiotic content, then the product packaging must be in accordance with consumer tastes, in this case consumers prefer dried yoghurt with a packaging of 7 grams and priced at 10.000.Based on the results of the decriminant analysis, it shows that out of 100 respondents, as many as 90 people will buy dried yogurt if dried yogurt is marketed. Then 4 people will not buy dried yogurt if it is marketed and 6 people are hesitant about the choice. Based on the descriptive results of the study, it was shown that out of 100 respondents there were 47 women and 53 men with large families totaling 4 people, with an average income and expenditure a month of Rp. 500.000 - Rp. 1.500.000.